Kebijakan Dividen Memoderasi Pengaruh Profitabilitas Dan Kebijakan Hutang Terhadap Nilai Perusahaan - Khaerunnisa, Enis; Rina Nuraeni, Ratu; Mahmudi, Bambang (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2022)
The purpose of this study is to determine the effect of profitability on firm value, to determine the effect of debt policy on firm value, to determine profitability on firm value with dividend policy as a moderating variable, to determine profitability on firm value with dividend policy as a moderating variable, and to determine the effect of debt policy on firm value with dividend policy as a moderating variable. in automotive and component sub-sector companies listed on the Indonesia Stock Exchange for the 2012-2021 period. The research method used in this study is a quantitative method and the source of data in this study is secondary data. The selection of the sample through the purposive sampling method, out of a total of 13 companies, there are 5 companies that meet the criteria as a research sample with 10 years of research so that the research data totals 50 observations. The hypothesis testing method in this study uses the panel data regression model with the Common Effect Model (CEM) approach and for testing the moderating variable using the Moderated Regression Analysis (MRA) model. Data analysis of both models uses the Eviews program version 10. Based on the results of the analysis it is known that profitability has a significant positive effect on firm value, debt policy has no significant effect on firm value, dividend policy is not able to moderate the effect of profitability on firm value, and dividend policy is not able to moderate influence of debt policy on firm value